Improving Student Creative Thinking Ability With Problem Based Learning Approach Using Hawgent Dynamic Mathematics Software - Shiwei Tan; Lingjie Zou; Tommy Tanu Wijaya; Neng Suci Septiani Dewi (Departement of Mathematics Education, 2020)
The main problem in this study is the lack of mathematical creative thinking abilities of elementary school students in Cimahi, Indonesia. This lack of mathematical creative thinking abilities is caused by an incorrect learning process. The teacher does not direct students to think creatively. In fact students still depend a lot on what is explained by the teacher in the class. The learning process with problem-based learning that is aided by hawgent dynamic mathematic software can direct students to think creatively. The population in this study were all elementary school students in Cimahi city. The samples were the students of elementary school Cimahi class 3A and 3B. The instrument in this study is descriptive test of students creative thinking abilities. This instrument was used to obtain data about students' creative thinking abilities with problem-based learning approach using hawgent dynamic mathematic software and by conventional learning. The data processed in this study was from the post-test score. These scores from both of the experimental class group and the control class group. Then, the data was processed by using SPSS 19.0 and Microsoft Excel. The data was analyzed using t-test statistic. The final result of this study concluded the achievement and improvement of creative thinking abilities of students whose learning problem-based approach using hawgent dynamic mathematic software.